Adaptive Crisis Management in Strengthening Institutional Resilience of Islamic Boarding Schools - Hasan, Mustaqim; Patimah, Siti; Murtafiah, Nurul Hidayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study examines the adaptive crisis management model and the institutional resilience of Pondok Pesantren Hidayatul Mubtadiin Jati Agung, an Islamic educational institution operating amid rapid disruption. The research analyzes pesantren crisis responses, identifies internal factors shaping institutional resilience, and explores the role of Islamic values in sustaining long-term stability. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation involving kyai, teachers, administrators, dormitory supervisors, and senior students, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings show that crisis responses are characterized by adaptive and collaborative management, rapid coordination, flexible structural adjustments, and strong spiritual–transformational leadership. Institutional resilience is reinforced by a deeply embedded organizational culture, structured mentoring, and high human resource commitment, which support continuity and shared responsibility during crises. Islamic values such as tawakal, patience, discipline, and musyawarah function as psychological stabilizers and normative guidelines that shape behavior and decision-making under pressure. However, the pesantren continues to face challenges, including limited formal crisis procedures, uneven technological literacy, and gaps in early risk detection. Overall, the study suggests that pesantren resilience is best conceptualized through a hybrid model integrating traditional Islamic values with modern crisis management principles to strengthen preparedness and long-term institutional sustainability.